Paleoclimate and ecology of Cretaceous continental ecosystems of Japan inferred from the stable oxygen and carbon isotope compositions of vertebrate bioapatite. (January 2021) - Amiot, Romain; Kusuhashi, Nao; Saegusa, Haruo; Shibata, Masateru; Ikegami, Naoki; Shimojima, Shizuo; Sonoda, Teppei; Fourel, François; Ikeda, Tadahiro; Lécuyer, Christophe; Philippe, Marc; Wang, Xu
Graphical abstract: Highlights: We reconstruct the paleoenvironments of five Cretaceous localities in Japan. Stable isotopes are used to infer surface temperatures and amount of precipitation. High-altitude precipitation contributed to local surface waters. Climate changed from cold and dry before the Aptian to warmer and more humid. Abstract: We investigated the environmental conditions that prevailed in continental ecosystems recorded in sedimentary deposits of Japan during the Cretaceous through the analysis of oxygen and carbon isotope compositions of phosphate (δ 18 Op ) and apatite-bound carbonate (δ 18 Oc and δ 13 Cc ) of vertebrate teeth and bones. Local surface water δ 18 Ow values were calculated using known phosphate-water isotope fractionation equations. Anomalously low δ 18 Ow values of local waters strongly suggest a significant contribution of high-altitude precipitation from nearby mountains to local surface waters. Mean air temperatures were estimated using a global meteoric water δ 18 Omw value – Mean Annual Air Temperature relationship, and compared to surface water temperatures estimated from fish apatite δ 18 Op values. Local mean annual precipitations (MAP) were estimated using the known relationship existing between MAP and C3 plant δ 13 Cp value, the latter being calculated using apatite-diet 13 C-enrichment applied to plant-eating sauropod and ornithopod dinosaur δ 13 Cc values. Reconstructed environmental conditions suggest that climate changed from cool temperate to warm temperate, being relatively cold and dry during the Late Hauterivian and Barremian to warmer and seasonally more humid during the Aptian and Albian, and even warmer during the Cenomanian-Coniacian. Proposed thermal evolution during the Early Cretaceous is compatible with the absence of thermophilic taxa such as crocodylomorphs before the Aptian in the fossil record of Japan.